1992
DOI: 10.1557/proc-280-173
|View full text |Cite
|
Sign up to set email alerts
|

Uhv-Mocvd Growth and in Situ Characterization of Epitaxial TiO2 Films

Abstract: Thin films of TiO2 were grown on SrTiO3 and Al2O3 using Ti(OC3H7)4 in the absence of any external oxygen source such as H2O or O2. On SrTiO3 (001), epitaxial anatase (001) formed even at temperatures (800 °C) above the anatase to rutile phase transition temperature. In situ reflection high energy electron diffraction (RHEED) was used to monitor structural evolution during growth, and the films were further characterized by Auger electron spectroscopy (AES), transmission electron microscopy (TEM), and x-ray dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 5 publications
1
13
0
Order By: Relevance
“…TiO 2 thin films have been grown on a wide range of oxide substrates, such as Al 2 O 3 [9][10][11], SrTiO 3 (STO) [11], and LaAlO 3 (LAO) [12]. Several growth techniques have been used, including metalorganic chemical vapor deposition (MOCVD) [9][10][11], sputtering [13,14], pulsed laser deposition (PLD) [15,16], and molecular beam epitaxy (MBE) [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…TiO 2 thin films have been grown on a wide range of oxide substrates, such as Al 2 O 3 [9][10][11], SrTiO 3 (STO) [11], and LaAlO 3 (LAO) [12]. Several growth techniques have been used, including metalorganic chemical vapor deposition (MOCVD) [9][10][11], sputtering [13,14], pulsed laser deposition (PLD) [15,16], and molecular beam epitaxy (MBE) [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…It is demonstrated that the alkoxide-based CVD www.elsevier.com/locate/jaap treatment combined with UV irradiation can improve the efficiency of dye-sensitized photoelectrodes with nanocrystalline TiO 2 deposited on ITO-coated plastic films [9]. The thermal decomposition reactions of TTIP and the deposition processes were studied in detail [10][11][12][13]. Ahn et al [14] demonstrated that the deposition occurs at a lower temperature in oxygen containing atmosphere than in nitrogen.…”
Section: Introductionmentioning
confidence: 99%
“…TTIP is chosen as the TiO 2 precursor due to its non-corrosivity and non-toxicity. Moreover, decomposition of TTIP to TiO 2 is a very clean process [10]. The structural, morphological, optical and photoelectrochemical properties are studied in order to utilize them in dye-sensitized solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…[29,30] At the same time, the reasonably smooth trend in the decomposition temperatures, including that of the methoxide, throws doubt on the general suggestion of beta-hydrogen elimination as the dominant decomposition mechanism because there are no b-hydrogens in the methoxide. Obviously other mechanisms, such as intermolecular elimination reactions involving another alkoxo group or surface-bound oxo or hydroxo groups, [31,32] must be operative in the case of the methoxide, and are likely to play a role with the other alkoxides also. However, one outcome of the comparative study on titanium alkoxides [28] was the identification of Ti(OMe) 4 as the most stable titanium alkoxide, thereby potentially allowing its use at higher temperatures than the other alkoxides.…”
Section: Introductionmentioning
confidence: 99%